Stress Amplification and Shielding of Double-Edge Cracks in Alveolar Bone Under Mode II Loading: A Comparative Analysis of Bone Material Heterogeneity: (Jurnal Mekanikal, 2025)
This paper aims to examine the response of double edge cracks in alveolar bone under Mode II loading with emphasis on differences in crack behaviour between homogeneous (cancellous) and heterogeneous (cortical-cancellous) bone types. Implant placement exerts load on the alveolar bone and consequently causes microcracks that would influence the stability of the implant and the bone. Such fractures and their relation to the composition of the human bones must be better understood to enhance the design of the implant. Crack behaviour was studied using a 2D continuum mechanics model of the dimension 1mm x 1mm. The crack length-to-width ratio of the upper crack varied in the range of 0.125 mm to 0.5 mm, and the lower crack was held constant at 0.125 mm. The goal of the study is to investigate Mode II loading of cancellous and cortical-cancellous bone materials where stress intensity factors (SIF) and normalized SIF values are a particular focus. In the homogeneous cancellous bone model, stress shielding occurred and normalized SIF values from 0.176 to 0.717 were consistently demonstrated. While the heterogeneous model initially showed similar shielding behavior (SIF ranging from 0.039 to 0.053), a transition was observed from shielding to stress amplification to SIF increasing from 0.053 to 1.205, with a unification point at a/W ≈ 0.3119. We observe that the cortical layer initially disperses the applied shear stress; however, as the crack length increases beyond a critical threshold, stress amplification occurs. Thus, the relevance of bone heterogeneity to the crack behavior is emphasized and the need to account for material composition in the implant design and placement for improving implant mechanical stability and durability is confirmed.
Keywords: Stress Intensity Factor (SIF), Bone Material Heterogeneity, Mode II Loading, Double-Edge Cracks, Fracture Mechanics.